Metabotropic Glutamate Receptors 7 within the Nucleus Accumbens are Involved in Relief Learning in Rats - Kahl, Evelyn (Curr Neuropharmacol, 2016)
Relief learning is an appetitive association of a formally neutral cue with relief induced by the offset of an aversive stimulus. Since the nucleus accumbens mediates relief learning and accumbal metabotropic glutamate receptors 7 (mGluR7) modulate appetitive-like processes, we hypothesized that accumbal mGluR7 may be involved in the modulation of relief learning. Therefore, we injected the allosteric mGluR7 agonist AMN082 into the nucleus accumbens and tested the effects of these injections on acquisition and expression of relief memory, as well as on the reactivity to electric stimuli. AMN082 injections blocked acquisition but not expression of relief memory. In addition, accumbal AMN082 injections strongly reduced the locomotor reactivity to electric stimuli indicating antinociceptive effects. These antinociceptive effects might be causal for the blockade of relief learning after AMN082 injections. Taken together, the present study indicates that functional activation of accumbal mGluR7 has antinociceptive effects that interfere with relief learning.